Singaporean pre-service music teachers’ identities, motivations and career intentions - Bennett, Dawn; Chong, E. (SAGE publishers, 2017)
This article explores pre-service music teachers’ professional identities during pre-service training. Its focus is a student cohort whose studies are funded by the Singaporean Ministry of Education in return for a commitment—a teaching bond or contract—to work as teachers in schools. An overview of pre-service teacher education and the challenges of attraction and retention in Singapore is followed by discussion of the literature relating to identity formation, with a focus on music teacher and musician identities. Next, analysis and discussion of the findings highlight that participants’ teacher identities did not align with their level of performance proficiency. Teacher identity did, however, align with participants’ intentions to remain in teaching; participants who defined themselves first and foremost as music teachers were more likely than their peers to plan long-term teaching careers. The article considers the influence of teaching bonds, or contracts, signed by students in advance of their post-secondary studies. It concludes by considering the implications for recruitment and for developing professional identity among pre-service music teachers.